Browning in foods - Ramanujam, S. (Defence Science Journal, 2014)
Browning is a serious problem particularly in respect of dehydrated foodstuffs. Taking into consideration the operational theatres in which our forces are deployed at present, the supply of dehydrated material has become a necessity. In view of this the problem of browning in the processed foods has assumed added importance. Browning results in the development of off-flavors and odours and loss in nutritive value. various causes leading to enzymic and non-enzymic browning are described as also a brief account of the current theories of browning. Methods of minimizing browning and increasing storage life of precooked foods are given.